Structural Assessment and Upgrading for an Old Building Belonging to an Historical Multi-Sports Center in Naples - Miano, Andrea; Chiumiento, Giovanni; Saggese, Angelo (Frontiers in Built Environment, 2019)
A significant number of non ductile existing reinforced concrete frame buildings, built in different seismic regions around the world but without adequate seismic detailing requirements, suffered damages or collapse after past earthquakes. In fact, these reinforced concrete frame buildings are much more susceptible to high level of damage or to collapse than modern code-conforming frames. A crucial issue in the community of the earthquake engineering is the assessment and the upgrading of these non ductile reinforced concrete structures. In particular, a careful assessment of the existing building is very important in order to understand the failure mechanisms that govern the achievement of predefined limit states or the collapse of the structure. Only after an in depth seismic assessment, the best upgrading/retrofit strategy can be designed and applied to the structure. In some cases, the historical value of these buildings makes the assessment procedure and the upgrading design more complicated due to the constraints related to the limited possibility of interventions. In this work, a building belonging to an old multi-sports center, is used as case study. The complex orbits around the soccer stadium called Collana and located in Naples. This soccer stadium was initially built in the late '20s and then it was completely rebuilt in the post-war period and used as a sports center for different sporting activities. Currently, the complex includes a soccer field, an athletic track, three indoor gyms, three tennis fields, a medical center sports and the indoor pool building investigated herein. The analysis of seismic vulnerability implemented for the case study building shows an unsafe condition under both static and seismic loads. The building upgrading is provided choosing the best strategy among different options in order to achieve a certain predefined threshold of the seismic safety for the building. Definitively, the paper presents a real upgrading design case study for a building belonging to an historical complex. Assessment and upgrading are shown both based on linear and dynamic non linear analyses procedures. Finally, the effectiveness of the structural interventions of upgrading is measured coherently with the new Italian guidelines for seismic risk classification of construction.